2020
DOI: 10.1080/03639045.2020.1791165
|View full text |Cite
|
Sign up to set email alerts
|

Formulation development of paracetamol instant jelly for pediatric use

Abstract: Objective: Paracetamol is a common antipyretic and analgesic medicine used in childhood illness by parents and physicians worldwide. Paracetamol has a bitter taste that is considered as a significant barrier for drug administration. This study aimed to develop an oral dosage form that is palatable and easy to swallow by pediatric patients as well as to overcome the shortcomings of liquid formulations. Methods: The paracetamol was encapsulated in beads, which were prepared mainly from alginate and chitosan thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…The conditions included a measuring temperature of 37 °C and a cone rotor (cone angle: 1°, cone diameter: 35 mm) with a gap of 1 mm. The flow behaviour was measured using the viscosity curve, and the graphs were then presented as viscosity (Pa.s) vs. the shear rate function (γ˙) and were fitted to a power-law model [ 54 ]. The viscoelastic behaviour of the gels was determined by an oscillatory amplitude sweep test which was carried out at a fixed frequency of 0.623 rad/s with shear stress ranging from 1 Pa to 100 Pa, in the linear viscoelastic region (LVR) of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…The conditions included a measuring temperature of 37 °C and a cone rotor (cone angle: 1°, cone diameter: 35 mm) with a gap of 1 mm. The flow behaviour was measured using the viscosity curve, and the graphs were then presented as viscosity (Pa.s) vs. the shear rate function (γ˙) and were fitted to a power-law model [ 54 ]. The viscoelastic behaviour of the gels was determined by an oscillatory amplitude sweep test which was carried out at a fixed frequency of 0.623 rad/s with shear stress ranging from 1 Pa to 100 Pa, in the linear viscoelastic region (LVR) of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Parasetamol memiliki rasa yang sangat pahit 7 . Agar sediaan parasetamol dapat disukai oleh anak-anak, maka parasetamol ditambahkan pemanis untuk menutupi rasanya 8 .…”
Section: Pendahuluanunclassified
“…Suppositories and syrups are the most used dosage forms in infants and children. Paracetamol has a bitter taste, which forms an obstacle for its administration to pediatrics and geriatrics where a large amount of the drug (from some hundreds of milligrams to 1 g) is needed for one dose; hence, it is important to mask the bitter taste of paracetamol upon administration to achieve good compliance [ 152 , 153 , 154 ]. In a comparison of paracetamol with phenacetin and acetanilide, which have a very slightly bitter taste and bitterless taste, respectively, it was found that the para position of the benzene ring is the only difference among these three compounds, where paracetamol has a hydroxyl group, phenacetin has an ethoxy group, and acetanilide has a hydrogen atom.…”
Section: The Prodrug Approachmentioning
confidence: 99%